Misleading Health Consumers Through Violations of Communicative Norms: A Case Study of Online Diabetes Education. (July 2018) - Powell, Derek; Keil, Martin; Brenner, Dru; Lim, Liliana; Markman, Ellen M.
Communication is a cooperative endeavor that goes well beyond decoding sentences' literal meaning. Listeners actively construe the meaning of utterances from both their literal meanings and the pragmatic principles that govern communication. When communicators make pragmatically infelicitous statements, the effects can be similar to paltering—misleading speech that evokes false inferences from true statements. The American Diabetes Association's (ADA's) "Diabetes Myths" website provides a real-world case study in such misleading communications. Calling something a myth implies that it is clearly false. Instead, the ADA's "myths" are false only because of some technicality or uncharitable reading. We compared participants' baseline knowledge of diabetes with that of participants who read either the ADA's myths or the myths rewritten as questions that do not presuppose the statement is false. As predicted, exposure to the ADA's "myths, " but not to the rephrased questions, reduced basic knowledge of diabetes. Our findings underscore the need to consider psycholinguistic principles in mass communications.